Factors that Affect the Intention to Use Mobile Banking in Sharia Banks - Devi Triana Rofianti; Sania Hanim Inayah; Lana Nisrina Nabila; Muad Eka Faza; Riyan Andni; Suxiang Anindya (Sharia Oikonomia Law Journal, 2023)
The background of this research is the mobile baking service, which is slowly being considered as a service that must be provided by banks to their customers. Thus, Sharia banks also adopt mobile banking services as a strategy to gain a competitive advantage. Service features, security, and convenience are analyzed to determine direct and indirect effects on the intention to use BSI Mobile (a mobile banking service from the largest Sharia bank in Indonesia). This research uses a type of quantitative research with primary data obtained from questionnaires or online surveys via Google Forms. The number of samples in this study was 100 respondents, namely BSI Mobile users. The data analysis technique used is SPSS 26 which includes the validity test, the reliability test, the multiple linear regression tests, the determinant coefficients test, the F-test, and finally the T-test. The results show that service features and perceived ease of use have a positive and significant effect on the intention to use BSI Mobile. However, security doesn't have a significant effect on the intention to use BSI Mobile. This study aims to help Sharia banks develop their mobile banking services, so they have a higher chance in competing with conventional banks.